Glycosylation of Glycolipids in Cancer: Basis for Development of Novel Therapeutic Approaches - Daniotti, Jose L.; Vilcaes, Aldo A.; Torres Demichelis, Vanina; Ruggiero, Fernando M.; Rodriguez-Walker, Macarena (Frontiers in Oncology, 2013)
Altered networks of gene regulation underlie many pathologies, including cancer. There are several proteins in cancer cells that are turned either on or off, which dramatically alters the metabolism and the overall activity of the cell, with the complex machinery of enzymes involved in the metabolism of glycolipids not being an exception. The aberrant glycosylation of glycolipids on the surface of the majority of cancer cells, associated with increasing evidence about the functional role of these molecules in a number of cellular physiological pathways, has received considerable attention as a convenient immunotherapeutic target for cancer treatment. This has resulted in the development of a substantial number of passive and active immunotherapies, which have shown promising results in clinical trials. More recently, antibodies to glycolipids have also emerged as an attractive tool for the targeted delivery of cytotoxic agents, thereby providing a rationale for future therapeutic interventions in cancer. This review first summarizes the cellular and molecular bases involved in the metabolic pathway and expression of glycolipids, both in normal and tumor cells, paying particular attention to sialosylated glycolipids (gangliosides). The current strategies in the battle against cancer in which glycolipids are key players are then described.